2015
DOI: 10.4252/wjsc.v7.i1.75
|View full text |Cite
|
Sign up to set email alerts
|

In vivoimaging of endogenous neural stem cells in the adult brain

Abstract: The discovery of endogenous neural stem cells (eNSCs) in the adult mammalian brain with their ability to self-renew and differentiate into functional neurons, astrocytes and oligodendrocytes has raised the hope for novel therapies of neurological diseases. Experimentally, those eNSCs can be mobilized in vivo , enhancing regeneration and accelerating functional recovery after, e.g., focal cerebral ischemia, thus constituting a most promising approach in stem cell research. In order to translate those current ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…Although they remain in a functional state within their specific niches throughout the lifespan of all mammals (Alvarez-Buylla & Garcia-Verdugo, 2002;Bond, Ming, & Song, 2015), the regenerative capacity of the brain is limited if substantial damage occurs (Alvarez-Buylla, Seri, & Doetsch, 2002;Sohur, Emsley, Mitchell, & Macklis, 2006). Promising research focuses on enhancing this innate regenerative capacity of the brain by explicitly targeting the endogenous NSC niche, for example, by pharmacological means (Rabenstein & Rueger, 2018;Rueger & Schroeter, 2015;Vay et al, 2016). However, research on NSC grown in cell culture always faces the problem of artificiality when compared with the in vivo situation because NSC functions crucially depend on the microenvironment in the stem cell niche (Doetsch, 2003;Regalado-Santiago, Juarez-Aguilar, Olivares-Hernandez, & Tamariz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although they remain in a functional state within their specific niches throughout the lifespan of all mammals (Alvarez-Buylla & Garcia-Verdugo, 2002;Bond, Ming, & Song, 2015), the regenerative capacity of the brain is limited if substantial damage occurs (Alvarez-Buylla, Seri, & Doetsch, 2002;Sohur, Emsley, Mitchell, & Macklis, 2006). Promising research focuses on enhancing this innate regenerative capacity of the brain by explicitly targeting the endogenous NSC niche, for example, by pharmacological means (Rabenstein & Rueger, 2018;Rueger & Schroeter, 2015;Vay et al, 2016). However, research on NSC grown in cell culture always faces the problem of artificiality when compared with the in vivo situation because NSC functions crucially depend on the microenvironment in the stem cell niche (Doetsch, 2003;Regalado-Santiago, Juarez-Aguilar, Olivares-Hernandez, & Tamariz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that several PET techniques may be able to identify human stem cells in stroke patients (55), and discriminate between nonviable and viable (penumbra) tissue, which may be relevant for future trials studying neuroprotective strategies (56).…”
Section: Future Developmentsmentioning
confidence: 99%
“…The presence of neural genesis in the brain of adults was confirmed in 1998, when Fred Gage and Swedish neurobiologist Peter Eriksson first demonstrated the formation of new neurons in the human hippocampus [14]. Today there is no doubt about the existence of permanent neurogenesis in some areas of the brain of adult mammals, which is provided by a pool of neural stem cells (NSCs) [7,8,32,38,49].…”
mentioning
confidence: 93%